A Navier–Stokes numerical wave tank with a pressure-based relaxation zone method. (15th December 2022) - De Vita, Francesco; Di Mascio, Andrea; Onorato, Miguel
Abstract: In the relaxation zone method for numerical wave tank modelling, the numerical fields are usually relaxed in the generation zone to the solution given by the potential theory. In the adopted procedure, the two-phase viscous flow is blended with the potential solution and this underlying inconsistency in the generation region can lead to instability in the flow. In this work, we present a new method for the wave generation in the context of the relaxation zone method which overcome the issue on the velocity forcing by introducing a body force equal to the potential pressure gradient. Results show that the method gives accurate results when compared with classical test case for wave propagation. Highlights: A modified relaxation methods based on pressure gradient forcing. The method produces proper vorticity field in the generation zone. The methods gives accurate results when compared with classical test cases.